Epigenetic risk stratification in juvenile myelomonocytic leukemia by targeted methylation analysis of the BMP4 locus - Ghanjati, Foued; Heck, Annika; Lebrecht, Dirk; Nöllke, Peter; Andresen, Felicia; Rotari, Natalia; Schoof, Marlou; Schönung, Maximilian; Lipka, Daniel B; Dworzak, Michael; De Moerloose, Barbara; Sukova, Martina; et al. (Clinical epigenetics, 2025)
Juvenile myelomonocytic leukemia (JMML) is a rare pediatric myelodysplastic/myeloproliferative neoplasm characterized by distinct epigenetic signatures that facilitate molecular classification. This study aimed to evaluate the diagnostic utility of locus-specific DNA methylation in the bone morphogenetic protein 4 (BMP4) gene as a single predictor of disease outcomes in a cohort of 111 children diagnosed with JMML, alongside 9 healthy controls. Methylation levels of BMP4, assessed through targeted bisulfite next-generation sequencing (bs-NGS), were heterogeneous within the JMML cohort and were significantly associated with clinical risk factors, such as patient age, and fetal hemoglobin (HbF) levels. A comparative analysis of BMP4 bs-NGS and genome-wide methylation array data revealed a strong positive correlation (p < 0.001). The sensitivity and specificity of BMP4 bs-NGS for classifying high-methylation cases were 0.612 and 0.887, respectively. For PTPN11-mutant patients (N = 40), the sensitivity was 0.667 and the specificity was 0.842. Survival analysis indicated that patients with high BMP4 methylation (BMP4h) had lower 5-year disease-free survival (DFS) rates than those with normal BMP4 methylation (BMP4n). Specifically, the 20% of patients with highest BMP4 methylation had a 5-year DFS of 0.38, in contrast to 0.62 for the lowest 20% (p = 0.007). These findings highlight the potential of BMP4 methylation analysis as a complementary biomarker for JMML risk stratification, mirroring genome-wide methylation profiles known to associate with prognostic subgroups.
Keywords: tyrosinfosfatasa nereceptorového typu 11; ženské pohlaví; mladiství; lidé; prognóza; epigeneze genetická; hodnocení rizik; Biomarker; kostní morfogenetický protein 4; studie případů a kontrol; Risk Assessment; Child; předškolní dítě; Abstract word count = 217; Child, Preschool; BMP4; Humans; DNA methylation; Prognosis; JMML; Epigenesis, Genetic; Case-Control Studies; juvenilní myelomonocytární leukemie; Infant; mužské pohlaví; Male; DNA Methylation; Leukemia, Myelomonocytic, Juvenile; kojenec; Protein Tyrosine Phosphatase, Non-Receptor Type 11; vysoce účinné nukleotidové sekvenování; Bone Morphogenetic Protein 4; Bs-NGS; Adolescent; metylace DNA; Risk stratification; Text word count = 3077; Female; dítě; High-Throughput Nucleotide Sequencing